Prevalence and Clinical Features of FOG in Chinese PD Patients, a Multicenter and Cross-Sectional Clinical Study - Gan, Jing; Liu, Weiguo; Cao, Xuebing; Xie, Anmu; Li, Wentao; Yuan, Canxing; Jin, Lirong; Liu, Suzhi; Jin, Lingjing; Guo, Dengjun; Shen, Yuefei; Wu, Yuncheng; et al. (Frontiers in Neurology, 2021)
Objectives: Freezing of gait (FOG) is generally considered as an independent symptom of Parkinson's disease (PD) with a complex pathophysiology. There is a wide range of associated clinical features of FOG reported from different studies without consistent conclusion. Thus, a multicenter, cross-sectional study was designed to investigate the prevalence and clinical features of FOG together with its unique contribution quality of life in Chinese PD patients. Methods: Eight hundred and thirty eight PD patients were consecutively recruited into this study from 12 hospital centers in six provinces in China. Clinical information, including motor and neuropsychological features as well as pharmacological details, was collected. Results: Of 827 PD patients, 245 (29.63%) reported FOG. The prevalence of FOG was strongly correlated with modified H-Y stages and symptomatic duration (p < 0.01). 84.90% freezers experienced FOG during turning and 88.98% experienced when initiating the first step. Compared with non-freezers, freezers reported longer disease duration (7.73 ± 5.44 vs. 4.69 ± 3.94, p < 0.000), higher frequent PIGD phenotype (61.22 vs. 35.91%, p < 0.000), higher scores of UPDRS III (32.85 ± 15.47 vs. 22.38 ± 12.89, p < 0.000), HAMA (10.99 ± 7.41 vs. 7.59 ± 6.47, p < 0.000), HAMD (15.29 ± 10.29 vs. 10.58 ± 8.97, p < 0.000) and lower MMSE score (25.12 ± 5.27 vs. 26.63 ± 3.97, p < 0.000), and higher daily levodopa dosage (432.65 ± 264.31 vs. 319.19 ± 229.15, p < 0.000) with less frequent initial use of dopaminergic agonist (8.57 vs. 14.78%, p < 0.05). Using binary logistic regression, the associated factors of FOG might be non-tremor dominant onset (OR = 3.817, p < 0.000), the presence of anxiety (OR = 2.048, p < 0.000) and imbalance (OR = 4.320, p = 0.012). Freezers had poorer quality of life than non-freezers and FOG impacted PDQ-8 independently. Conclusion: Nearly one third of the PD patients experienced FOG. Its frequency increased with PD progression and FOG reduced independently the quality of life. Non-tremor dominant, disease progression, and anxiety were risk factors of FOG.